ANALISIS YURIDIS TERHADAP PUTUSAN MAHKAMAH AGUNG NO: 124K/ TUN/2013, TENTANG TERBITNYA IZIN MENDIRIKAN BANGUNAN DI ATAS TANAH YANG MASIH DALAM SENGKETA DI PENGADILAN TATA USAHA NEGARA MEDAN - Deliana Simanjuntak; Budiman Ginting; Sunarmi Sunarmi; Jusmadi Sikumbang (Universitas Sumatera Utara, 2015)
ABSTRACT Building permits rising over disputed land in State Administrative Court Medan. Before the building permit is issued, Plaintiff reported to the local office of spatial and building code field on the status of the land is still in the process of law (debatable), but the Agency for Spatial and building overlook the claimant report, which should Spatial Agency and the building had to postpone publication Building permit because there are reports plaintiff. Then Building permit issuance is not in accordance with the Decree Mayor of Medan No. 34/2002 junto Regional Regulation of Medan No. 5/2012 about Retribution Building permits, Article 13, point (b) Issuance of Building Permit may be delayed if there are complaints about land disputes or no legal proceedings in the building or land, either in written form or orally. The judges made a different decision: Administrative Court of Medan to cancel the building permit, and the State Administrative High Court of Medan supports the decision the Administrative Court of Medan, but the verdict of the Supreme Court rejected the verdict Administrative High Court of Medan rejected the lawsuit and the Plaintiff. The verdict difference need to be analyzed and researched to find the correct legal value. Keywords: Issuance of Building Permit on a Disputed Land